FEATURES OF FOLIAGE HARVEST OF LEAFY RADISH DEPENDING ON DENSITY OF PLANTS GROWN - A.F. Eliseev; O.V. Eliseeva; T.M. Seredin (Овощи России, 2011)
Expanding the range of leafy and salad vegetables and extension of their production and consumption are indicators that can characterize the state and prosperity of the nation. The great value and indispensable of vegetables in human's diet are that they are the sources of vitamins, sugars, organic acids, mineral salts, microelements and biologically active matters which determine the taste of food and its assimilation in human's body.